Andreas Barthivs Ad D. Catharinae Pastor. Obiit Natvs Annos LVIII. / Leonhard Heckenauer. - Heckenauer, Leonhard (165.-1704?) (1702)
Przedstawia portret Andreasa Bartha, pastora kościoła św. Katarzyny w Gdańsku.